2021
DOI: 10.1093/ndt/gfab084.009
|View full text |Cite
|
Sign up to set email alerts
|

Mo336renal Contrast-Enhanced Ultrasound (Ceus) to Evaluate Early and Chronic Modifications of Renal Perfusion and to Predict Renal Dysfunction After Renal Ischemia-Reperfusion in Mice

Abstract: Background and Aims Renal ischemia-reperfusion can lead to acute kidney injury (AKI), increasing the risk of developing chronic kidney disease (CKD) through inflammation and vascular lesions. Serum urea or creatinine level routinely used as diagnostic indices of renal function are always delayed from the onset of the disease. Therefore, we currently lack reliable markers to early detect AKI, especially in animals. We aimed to show that non-invasive renal contrast-enhanced ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Quantitatively, compared with the healthy mice (ischemia time: 0 min), the normalized PA intensity decreased by 21.5% at 10 min post treatment with ischemia reperfusion ( p < 0.01). These results demonstrated that the developed nanoantennas enabled the detection of AKI occurrence in mice at a time as early as 10 min post treatment with ischemia reperfusion, around 2 orders of magnitude earlier than most established probes. …”
Section: Resultsmentioning
confidence: 81%
“…Quantitatively, compared with the healthy mice (ischemia time: 0 min), the normalized PA intensity decreased by 21.5% at 10 min post treatment with ischemia reperfusion ( p < 0.01). These results demonstrated that the developed nanoantennas enabled the detection of AKI occurrence in mice at a time as early as 10 min post treatment with ischemia reperfusion, around 2 orders of magnitude earlier than most established probes. …”
Section: Resultsmentioning
confidence: 81%